Pengembangan Media Pembelajaran Berbasis Game Edukatif Menggunakan Aplikasi Educaplay Pada Materi Perubahan Wujud Zat Pada Mata Pelajaran IPA Kelas V SD - Amran, Muhammad (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This development research aims to produce an educational game–based learning media using the educaplay application for the topic of changes in the state of matter in fifth-grade science learning. the study was motivated by students’ low interest and difficulties in understanding abstract scientific concepts, as well as the limited use of digital learning media in schools. the research was conducted at sdn 213 hulo and sdn 63 cilallang, bulukumba regency, employing the addie model consisting of analysis, design, development, implementation, and evaluation stages. data were collected through interviews, observations, expert validation, and small- and large-scale tryouts. validation by material and media experts indicated that the product was in the highly feasible category after minor revisions in content and visual design. the small-scale tryout involving 10 students showed very positive responses and ease of use. the large-scale tryout with 30–40 students revealed that more than 80% of students found the media attractive and helpful for understanding the concepts. teachers also reported that the media enhanced student engagement and facilitated the learning process. classroom implementation demonstrated increased motivation and improved learning outcomes, as shown by students’ game scores and final assessments.the findings indicate that the educational game–based learning media developed through educaplay is valid, feasible, engaging, and effective, and can be used as an innovative alternative to support conceptual understanding of the changes in the state of matter. this study provides novelty through the systematic integration of educaplay’s interactive features into elementary science learning using the addie model, supported by multi-layered evaluation through expert validation, small-scale trials, and large-scale implementation.